Impact on access to education for students of III cycle and diversified education, with visual impairments in public education in Costa Rica, as a consequence of COVID-19, during the 2020 school year - Madrigal Flores, María del Socorro (2021)
The objective of this study was to analyze the impact produced on access to education of III cycle and diversified education students with visual impairments in public education in Costa Rica, during the 2020 school year, as a consequence of COVID- 19. The research design was phenomenological, so it was considered that the most appropriate instrument was the in-depth interview. The research subjects were six students with visual impairment, three women and three men, with blindness and low vision, enrolled in III Cycle and in diversified education, in the Costa Rican public educational system and that at the time of the research, in parallel, they received support from the Helen Keller National Education Center. Among the main findings is the importance of cooperative work among the support networks that students with visual impairment must have to face combined education with probability of success, and the emergence of a new social gap in families brought by the pandemic, that is, that which is related to the lack of connectivity and technological resources. One of the main conclusions that the research found is that students with visual impairments cannot be located in one of the particular settings for the combined education proposed by the Ministry of Public Education, as they require different formats at the time of presenting the didactic material for them to have access to an education that adjusts to their visual condition.